Integration of Bioinformatics and in vitro Analysis Reveal Anti-leishmanial Effects of Azithromycin and Nystatin - Jehangir, Irum; Ahmad, Syed F.; Jehangir, Maryam; Jamal, Anwar; Khan, Momin (Current Bioinformatics, 2019)
Background: Leishmaniasis is the major cause of mortality in under-developed countries. One of the main problems in leishmaniasis is the limited number of drug options, resistance and side effects. Such a situation requires to study the new chemical series with anti-leishmanial activity. Objective: To assess the anti-leishmanial activity of antibacterial and antifungal drugs. Methods: We have applied an integrative approach based on computational and in vitro methods to elucidate the efficacy of different antibacterial and antifungal drugs against Leishmania tropica (KWH23). Firstly these compounds were analyzed using in silico molecular docking. This analysis showed that the nystatin and azithromycin interacted with the active site amino acids of the target protein leishmanolysin. The nystatin, followed by azithromycin, produced the lowest binding energies indicating their inhibitive activity against the target. The efficacy of the docked drugs was further validated in vitro which showed that our bioinformatics based predictions completely agreed with experimental results. Stock solutions of drugs, media preparation and parasites cultures were performed according to the standard in-vitro protocol. Results: We found that the half maximal inhibitory concentration (IC50) value of dosage form of nystatin (10,000,00 U) and pure nystatin was 0.05701 μM and 0.00324 μM respectively. The IC50 value of combined azithromycin and nystatin (dosage and pure form) was 0.156 μg/ml and 0.0023 μg /ml (0.00248 μM) respectively. It was observed that IC50 value of nystatin is better than azithromycin and pure form of drugs had significant activity than the dosage form of drugs. Conclusion: From these results, it was also proven that pure drugs combination result is much better than all tested drugs results. The results of both in vitro and in silico studies clearly indicated that comparatively, nystatin is the potential candidate drug in combat against Leishmania tropica.
Keywords: IC50